PENGARUH PUPUK KOMPOS DARI LIMBAH PADAT INDUSTRI PULP DAN KERTAS TERHADAP PERTUMBUHAN Eucalyptus pellita - Lesmana, Muhammad Reza; Ratnaningsih, Ambar Tri; Suhesti, Eni (Wahana Forestra: Jurnal Kehutanan, 2017)
The pulp and paper industry produces liquid waste in its production process. Liquid waste in solid form of sludge can be utilized as compost fertilizer. Research conducted at PT. Indah Kiat Pulp and PT Arara Abadi Rasau Kuning District, Riau Province. The aim of this research is to know the effect of compost fertilizer from pulp and paper industry waste on Eucalyptus pellita growth and to determine the most appropriate dose of compost for growth of Eucalyptus pellita. The research method was done by applying compost in 3-month Eucalyptus pellita with dosage of o gram, 750 gram, 1000 gram and 1250 gram. Parameters measured over 3 months were plant height, plant diameter and number of leaves. Provisi on of compost fertilizer from pulp and paper industry waste has no significant effect on Eucalyptus pellita growth. Visually, the most appropriate dose of compost for the growth of Eucalyptus pellita is a dose of 1000 grams.